PRIORITAS WILAYAH BERDASAR FAKTOR KONTEKTUAL UNTUK MENINGKATKAN NILAI INDEKS PEMBANGUNAN KESEHATAN MASYARAKAT DI SUMATERA SELATAN - Retnaningsih, Ekowati (Publikasi Penelitian Terapan dan Kebijakan, 2011)
Public Health Development in Indonesia has been measured by Public Health Development Index (PHDI). This index uses 24 health indicator base on health community survey and it is available to know the effectiveness health program in a region area or district. The aim of this study was to know the priority district in South Sumatera that has relation with PHDI. Design of the study was ecology study and cross sectional design. The result of the study shaws that there were two district as first priority district to do intervention for improving health access, education level, and reduce the poor proportion in their area. The district means were Musi Rawas and OKI.